TARGARONA BORRAS, Judit; SÁENZ-BADILLOS, Ángel (eds.), Jewish Studies at the Turn of the Twentieth Century, Proceeding of the 6th EAJS Congress, Toledo, 1998. Volumen 1: Biblical, Rabbinical, and Medieval Seudies,octubre, 1999. Volumen II: Judaism from - García Lozano, Raquel (Anaquel de Estudios Árabes, 1999)
Sin resumen